Cultural Heritage in a Changing World - Borowiecki, Karol Jan; Forbes, Neil; Fresa, Antonella (Springer Nature, 2016)
Cultural Heritage; Cultural Economics; Cultural Studies; Archaeology; Information Storage and Retrieval; Information Systems Applications (incl. Internet)